STRESS RELATED ORAL MANIFESTATIONS IN A GROUP OF PATIENTS FROM CONSTANȚA COUNTY - Steliana-Gabriela Buștiuc; Raluca Briceag; Gheorghe Raftu; Elena-Claudia Sin; Aureliana Caraiane (Romanian Journal of Oral Rehabilitation)
The purpose of this article is to evaluate the frequency of oral manifestations in patients with an increased level of stress. The study group included 52 patients from Constanța who arrived for specialized consultation. The patients were examined using conventional light and a clinical diagnosis was formulated based on the examination and findings. Following the clinical examination and the correlation with the anamnesis, the following types of manifestations of the oral mucosa were diagnosed: traumatic ulcers 33.33%, burning mouth syndrome – 17.65%, xerostomia – 13.73%, recurrent aphthous stomatitis – 11.76 %, herpetic oral infection – 11.76%, oral lichen planus – 7.84% and mucocele – 5.88%. Patients aged between 40-50 years presented the most frequent traumatic ulcers of the oral mucosa – 23.08% of all detected oral lesions. The most frequently reported oral manifestations detected in the male sex are represented by: traumatic ulcers – 21.15%, burning mouth syndrome – 11.54%, herpetic infections and xerostomia – 7.69%. Oral mucocele – 3.85% and recurrent acute aphthous stomatitis – 5.77% were detected the most in the female sex. All cases of oral lichen planus were identified exclusively in female patients. Bruxism was identified in 21 patients, over half being diagnosed in men, while myofacial pain dysfunction syndrome was detected in 11 patients, of which 7 were female. Stress can be a contributing factor in the appearance of oral manifestations, among which oral lichen planus is a premalignant lesion. All oral manifestations detected in patients exposed to stress can affect the functionality of the orofacial system and the quality of life.